Exosomal ncRNAs in liquid biopsy: a new paradigm for early cancer diagnosis and monitoring - Ghani, Muhammad Usman; Du, Liang; Moqbel, Abdulkareem Qasem; Zhao, Erhu; Cui, Hongjuan; Yang, Liqun; Ke, Xiaoxue (Frontiers in Oncology, 2025)
Cancer’s aggressive nature and delayed diagnoses often result in poor prognoses and limited treatment outcomes. Early detection, personalized treatments, and effective monitoring are essential for improving cancer management. Traditional tumor biomarkers, such as beta-2 microglobulin and Carcinoembryonic Antigen (CEA), are often yield inaccurate and inconclusive results. Recently, exosomal cargoes, especially non-coding RNAs (ncRNAs) such as microRNAs (miRNAs), long non-coding RNAs (lncRNAs), and circular RNAs (circRNAs), have gained attention as promising tools for the early, non-invasive detection of cancer. For instance, serum exosomal long ncRNA FOXD2-AS1 has demonstrated promising diagnostic potential in colorectal cancer (CRC), achieving an overall AUC of 0.736 across all patients and an improved AUC of 0.758 specifically for early-stage CRC, highlighting its effectiveness as a stage-specific biomarker for early detection and clinical assessment. Similarly, exosomal lncRNA-GC1 has effectively distinguished gastric cancer patients from controls and related conditions, with AUCs exceeding 0.86, thereby outperforming traditional markers such as CA 72-4, CEA, and CA19-9, which all scored below 0.79. Despite their great potential, the clinical application exosomal ncRNAs remains limited. This review highlights recent advancements in exosomal ncRNA research and their potential as diagnostic markers, addressing both the opportunities and challenges for clinical implementation.